Case Studies of Agri-Processing and Contract Agriculture in Africa - Sautier, Denis; Vermeulen, Hester; Fok, Michel; Biénabe, Estelle (World Bank, Washington, DC, 2012)
This paper reflected upon a wide range of situations in the evolution of the agroprocessing sector and its relations with farmers, in the context of national and international enabling policies. It highlights the importance or potential of contractual arrangements for governing the relationships between small and medium farmers and agroprocessors. The effectiveness of contracts has been shown to vary under different market settings and different markets agents. This paper illustrates the capacity of farmers-to-processors linkages in Africa to foster the effectiveness of agricultural growth for poverty reduction, make advantage of untapped sources of growth and generate pro-poor development through adequate institutions.